ANALISIS POLA KERJASAMA ORANG TUA DAN GURU SEKOLAH DASAR DI ACEH BARAT SELAMA PANDEMI COVID-19: ANALISIS POLA KERJASAMA ORANG TUA DAN GURU SEKOLAH DASAR DI ACEH BARAT SELAMA PANDEMI COVID-19 - Monitasari, Aulia; Husna, Faizatul; Jamin, Hanifuddin (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2021)
School and family are important factors for student achievement, so they must collaborate with each other. However, the Covid-19 pandemic that has occurred has made students and teachers switch from face-to-face classes to virtual classes. This also changes the pattern of collaboration between schools and parents. Using the 6 types of collaboration by Epstein (1997), this study aims to investigate the patterns of collaboration that occur between teachers and schools during a pandemic. The method in this research is qualitative using purposive sampling technique. Interviews were conducted on principals, teachers and parents of students. The results showed that there were differences in the pattern of cooperation before the pandemic and during the pandemic, where there were a number of types of cooperation that did not occur during the pandemic.